PRAKTIK DAN MOTIVASI MERUQYAH DENGAN AYAT KURSI - Ahmadi, Ahmadi (Reflektika, 2020)
Exorcism is a culture and heritage that must be preserved as an effort for Muslims to serve the community. The existence of exorcism in Indonesia has an important role, this is because in the life of Indonesian people there are two types of diseases, namely; ordinary and extraordinary diseases. In this extraordinary disease, exorcism has a role in society.This research is a qualitative research with a case study that seeks to reveal the practice and motivation of a person to become a exorcismer by using Ayat Kursi as a medium of ruqyah. In doing treatment, exorcismer uses readings from the Qur'an and hadith to treat someone's illness. One of the verses read in medicine is Ayat Kursi, which is a verse that has many fadilah and its virtues as a protective fortress for its readers, the greatest verse, the leader of the verses of the Qur'an. While the motivation to become exorcismer is to help others as an effort to get closer to Allah.